The Effect of Price and Product Quality On Purchase Decisions For Imported Used Clothing (Riwayat: Educational Journal of History and Humanities, 2026)
This study aims to determine the effect of price and product quality on purchasing decisions on imported used clothing in Sampit City. This study used purposive sampling technique. Respondents of this study amounted to 120 people. The analysis technique used in this research is multiple linear regression analysis using SPSS sofware version 22. The test results for the Price variable (X1) are equal to 0.008